Biblical names in Ukraine: regional aspects - Nasakina, Svitlana (Onomastique depuis l'Amérique Latine, 2024)
This paper presents a study of the Biblical names in regional and historical aspects. Throughout history the Bible has served as the most important religious book for many people. As a result, the Bible has had a significant impact on various aspects of culture, education, and traditions. Ukraine has been characterized by the use of the Biblical names since the adoption of Christianity which influenced on the whole history of the state. Since Biblical personal names are both the lexical units and the symbols, it is interesting to see the presence of these names in different regions and epochs. The present study aims at pointing out at regional aspects of Biblical personal names. The paper provides a brief overview of naming trends in the assignment of Biblical names and Christian names in Ukraine. Our database of all names was fed the names of 2,000 people. The material is taken from the list of students who studied at Odesa State Agrarian University from 2014-2024 with the help of a continuous sampling method. The methodology, both statistical and qualitative, had two phases: a) comparison of the ratio of Biblical names to non-Biblical names, and b) classification of discovered Biblical names. This research is just one aspect of a series of investigations whose goal is to describe the anthroponomical system of Odesa, Ukraine in diachronic and synchronic format. The findings suggest that personal names with Biblical origin continue to be widely used in Ukraine. We emphasize that the study of anthroponyms in different regions and epochs is a valuable tool for understanding the history and cultural traditions of Ukraine. Therefore, the importance of onomastics as an interdisciplinary science affecting History, Sociology, Theology, Literature, and regional studies in the research of the Biblical names in current and past Ukraine is shown. This study draws upon three theoretical frameworks: anthroponomastics (Felecan & Mihali, 2023; Piddubna, 2021, etc.), socio-onomastics (Ainiala, 2016; Beley, 2019, etc.), and the regional onomastics (Braychenko, 2019; Buga, 2013; Chuchka, 1970; Frai, 2021; Matsyuk, 2021; Sholia, 2018, etc.).